The Self Access Centre as Mass Customization - Farmer, Frank (Linguistik Online, 2012)
This paper describes the Self Access Centre (SAC) at the Universidad de Quintana Roo and presents the research support for the model in terms of mass-customization. The SAC with its systems, materials, activities and tutor support may be described as offering mass-customized language education. Tutor support is conceived in systemic terms as mass-customization, but as provider of professional advice in support of students’ own learning projects and facilitator of feedback in productive skills, tutor support is highly individualized. However, the mass-customization element makes individualization efficient and achievable.